Correlation of microbilirubin with total serum bilirubin and transcutaneous bilirubin - Nanthida Phattraprayoon; Kamonwan Soonklang; Peeraya Amnucksoradeja; Tanin Pirunnet (PLoS ONE, 2025)
Jaundice is a common condition in newborns that requires early detection. Screening for neonatal jaundice involves measuring microbilirubin (MB), total serum bilirubin (TSB), and transcutaneous bilirubin (TcB). This study aimed to examine the correlation between bilirubin levels obtained from these three measurements: MB, TSB, and TcB. The cross-sectional study included infants with a gestational age (GA) of 35 weeks or more who met the criteria for jaundice screening or exhibited signs of jaundice. Bilirubin levels were simultaneously measured using MB, TSB, and TcB at both the forehead and sternum. Statistical analysis was performed using Spearman’s rank correlation coefficient and a Bland-Altman plot. The study included 212 newborns, with 876 measurements (219 datasets). The mean GA ± standard deviation (SD) was 38.31 ± 1.14 weeks, the mean birth weight ± SD was 3094.17 ± 382.18 grams, and the mean age at the time of bilirubin measurement ± SD was 59.8 ± 16.3 hours. The mean ± SD of TSB were 10.42 ± 2.75 mg/dL, with a range of 1.75–20.52 mg/dL. Strong correlations were observed between MB and TSB (r = 0.96, p < 0.001), MB and TcB at the forehead (r = 0.85, p < 0.001), and MB and TcB at the sternum (r = 0.88, p < 0.001). TSB showed good correlations with TcB at both the forehead (r = 0.87, p < 0.001) and sternum (r = 0.90, p < 0.001), as well as correlation between TcB measurements at the forehead and sternum (r = 0.91, p < 0.001). The Bland-Altman analysis demonstrated good agreement between paired bilirubin measurements. The areas under the curve (AUC) for MB and TcB at both the forehead and sternum across three TSB thresholds (>10 mg/dL, > 12 mg/dL, and >15 mg/dL) were all above 0.9, with sensitivity and specificity ≥ 80%. These findings suggest that MB and TcB are useful screening tools in routine practice; however, TSB should still be used to confirm results for the clinical management of neonates with jaundice. Trial registration: Thai Clinical Trials Registry TCTR20231101004